Metaphorical Expressions of ‘Limits’ Concepts in Academic Legal Written Language - Gedzevičienė, Dalia (Respectus Philologicus, 2015)
The conceptualization of limits in academic legal written language is the focus of the present article. The main problem of the research is the controversial evaluation of such metaphorical expressions from the normative point of view. In academic legal papers, the upper limit of various payments is named as ‘ceiling’. Thus, the implemented conceptual metaphor shows that THE SYSTEM OF SOCIAL SECURITY IS A ROOM. In the same papers, the minimal limit of incomes of inhabitants and of lawbreaker at which some social measures are applied or at which some sanctions start to take effect is named as ‘threshold’. Therefore, these metaphorical expressions implement the conceptual metaphor CIRCUMSTANCES (OF INHABITANT OR OFFENDER) IS A ROOM. Though the figurative meanings of both ‘ceiling’ and ‘threshold’ in the Lithuanian language had formed due to the impact of foreign languages; the figurative meanings of the word ‘threshold’ are included in the dictionaries as the correct ones, but the expressions with ‘ceiling’ are evaluated like semantic calques.
Keywords: conceptual metaphor; functions of metaphor; figurative meaning; law; standard language norm